Motor and Non-motor Neurologic Symptoms of Wilson’s Disease: Exploring the Associations - Arka Prava Chakraborty; Adreesh Mukherjee; Uma Sinharoy; Madhushree Chakrabarty; Mainak Sengupta; Jasodhara Chowdhury; Atanu Biswas (Annals of Indian Academy of Neurology)
Background and Objectives: Although the motor symptoms of Wilson’s disease have received particular attention from researchers and medical professionals, non-motor symptoms might become increasingly prevalent with the advancement of the disease and can even appear before the onset of motor symptoms. However, clinicopathological correlations for most of these non-motor features are still poorly understood. The correlations between non-motor and motor symptoms have been examined in this study. Methods: Fifty patients with Wilson’s disease participated in this study. Each subject was administered the Global Assessment Scale and the Non-Motor Symptom Questionnaire (NMS Quest) for the assessment of motor and non-motor symptoms, respectively. Cognitive functions were evaluated with Addenbrooke’s Cognitive Examination III (Bengali version) and the Digit Span Test. Sleep-related problems were assessed with Pittsburgh Sleep Quality Index. Results: Of the patients who participated in this study, 82%, 56%, 90%, 18%, 82%, 8%, 60%, 56%, and 66% had digestive, urinary, apathy–attention–memory, hallucinations/delusions, depression/anxiety, sexual function, cardiovascular, sleep disorder, and miscellaneous (pain, weight, swelling, sweating, and diplopia) symptoms, respectively. NMS-Digestion (P ≤ 0.001), NMS-Urinary (P = 0.007), NMS-Miscellany (P = 0.001), NMS-Memory (0.011), and NMS-Sleep Disorder (P = 0.031) significantly predicted parkinsonism. NMS-Digestion was a significant predictor of dystonia (P < 0.001). Conclusion: Awareness regarding non-motor symptoms and their associations with motor symptoms might help physicians develop more efficient treatment regimens that can alleviate non-motor symptoms which can be equally troublesome and disabling for these patients. Management of non-motor symptoms is crucial for the overall well-being of these patients.